Silver-doped active carbon spheres and their application for microbial decontamination of water. Issue 4 (April 2022) - Chandra Joshi, Harish; Dutta, Dhiraj; Gaur, Nisha; Singh, G.S.; Dubey, Rama; Dwivedi, S.K.
Abstract: Highly efficient and durable, silver nanoparticles doped Active Carbon Spheres ACS(Ag) were synthesized by carbonization and activation of silver exchanged resins. The silver exchanged resins were prepared by exchanging H + ions of polystyrene sulphonate resin with Ag + ions of silver nitrate (AgNO3 ). The quantity of Ag + in the spheres was controlled by varying the concentration of AgNO3, from 0.0125 to 0.1 M. With increasing molar concentration of AgNO3, the effective intake of Ag + by the sphere increases from 1.1 to 8.1 weight percent (wt %). For activation, the spheres were incubated in the CO2 atmosphere for 6 h at fixed soaking temperature i.e. 1123 K. The characterization of synthesized silver doped ACS was performed by using different sophisticated instrumental techniques. The antimicrobial activity of silver doped ACS was studied against different bacterial strains like, E. coli, B. subtilis and Staphylococcus aureus . The study demonstrated that the zone of inhibition for E. coli was 16.9 ± 0.7 mm while for B. subtilis it was 17.1 ± 0.3 mm at a concentration of 8 mg of synthesized material. In addition, satisfactory results were obtained in shake flask and filtration test experiments also, even at a low concentration of 2 mg, showing growth inhibition of 94% for E. coli and 93% for B. subtilis . When the concentration of silver doped ACS was increased to 8 mg, complete removal of both the bacteria was observed after 24 h (100 % reduction for E. coli and B. subtilis ). Furthermore, when silver doped ACS was tested against Staphylococcus aureus according to ASTM:E 2149-01 method, biocidal activity of up to 73% was observed. Therefore, the silver doped ACS can be considered as a potential biocidal material for the studied bacterial strains and hence find suitable application for decontamination of water. Graphical abstract: Image 1 Highlights: Novel low-density silver doped active carbon spheres (ACS) were synthesized successfully. Characterization and antibacterial activity was examined for water decontamination application. Results revealed that the material effectively reduced microbial load by 99.9 %. Abstract : Silver nanoparticles, Resin, Carbonization, Activation, Antimicrobial assay.